PENGARUH STRATEGI PEMBELAJARAN STAD DAN STRATEGI PEMBELAJARAN EKSPOSITORI SERTA MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PPKn - Ria Rizki Agustini (Al-Mubin, 2018)
The purpose of this study was to examine (1) the differences in student PPKn learning outcomes who were taught using STAD cooperative learning strategies and Expository learning strategies, (2) the effect of the interaction between the use of learning strategies and learning motivation on learning outcames, (3) differences in student PPKn learning outcomes with high learning motivation those who are taught with STAD learning strategies and those that are taught with Expository learning strategies, (4) Differences in the learning outcomes of students with low learning motivation who are taught using STAD learning strategies and those taught with Expository learning strategies. The method used in this research is the experimental method with a 2 x 2 factorial design. The sample consisted of 2 classes, one experimental class, namely class X.2 totaling 22 students, one control class namely class X.1 totaling 22 students. The sampling technique is random sampling. The data analysis technique used in this research is descriptive statistical analysis techniques and inferential statistical analysis using the two-way Analysis of Variance (ANOVA) technique with the help of SPSS 23. The results and conclusions of the study were obtained (1) The learning outcomes of PPKn using STAD learning strategies were higher than those of Expository Learning strategies. Fcount and sig. amounted to 4,627 and 0.038. The value of Ftable at a significance of 0.05 is 4.07. The value of Fcount> Ftable or 4.627> 4.07, and the value of sig. 0.038 <0.05; (2) There is an influence of interaction between learning strategies and student motivation on learning outcomes of PPKn. The results of the anava calculation obtained the value of Fcount and sig. amounting to 44,207 and 0,000. The value of Ftable at a significance of 0.05 is 4.07. The value of Fcount> Ftable or 44.207> 4.07, and the value of sig. 0.00 <0.05; (3) The learning outcomes of highly motivated students who are taught with STAD learning strategies are higher than those taught with Expository learning strategies. The value of t count is 7.857, the value of t table at a significance of 0.05 is 2.086. The value of t count> t table or 7.857> 2.086, and sig.0.00 <0.05; (4) The learning outcomes of students with low motivation who are taught with the Expository learning strategy are higher than the STAD learning strategies. The t value is 2.714 and. The value of t table at a significance of 0.05 is 0.013. Because the value of t count> t table or 2.714> 2.086, and sig. 0.013 <0.05